AN EFFECT OF ORGANIC COMPOSTING DUCK MANURE AND POC HOUSEHOLD WASTE ON PLANT PRODUCTION SHALLOT (Allium Ascalonicum L) - Nisa, Khairun; Tarigan, Ruth Riah Ate; Luta, Devi Andriani (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Efforts to optimize the growth and productivity of shallot plants (Allium ascalonicum L) by applying organic compost of duck manure and POC of household waste. This research method used a factorial randomized block design (RBD) consisting of 2 treatment factors. The first factor was the application of duck manure organic compost (B), namely B0 = 0 g/planting hole, B1 = 50 g/planting hole, B2 = 100 g/planting hole and B3 = 150 g/planting hole. The second factor was the provision of POC for household waste (L), namely L0 = 0 ml/planting hole, L1 = 50 ml/planting hole, L2 = 100 ml/planting hole, L3 = 150 ml/planting hole. Parameters observed were the number of tillers (saplings), dry tuber weight per sample (g) and dry tuber weight per plot (g). The results showed that the application of duck manure organic compost had a very significant effect on the parameters of the number of tillers (saplings), dry production per sample (g) and dry production per plot (g). Where is the best treatment onB3 = (150 g/planting hole). PPOC distribution of household waste and their interactions had no significant effect on the parameters of the number of tillers (saplings), dry production per sample (g) and dry production per plot (g).